They came to baghdad - Christie, Agatha (HarperCollins London, 2003)
Baghdad is the chosen location for a secret superpower summit. But the word is out, and an organisation in the Middle East is plotting to sabotage the talks. Victoria Jones gets involved in the situation but gets more adventure than she bargained for